The Role of Job Satisfaction and Work Stress On Turnover Intention: The Mediating Role of Organizational Commitment - Raihands Adjie Saputra; Fauji Sanusi; Ali Imron (PT. Maju Malaqbi Makkarana, 2026)
The purpose of this study is to investigate the relationship beetween job satisfaction and work stress on turnover intention as well as organizational commitment mediates this reliationship. To gather study data, the questionnaire was used to poll 100 individuals. Structural Equation Modeling (SEM) was the method used in this quantitive study. SmartPLS version 4.1.1.6 with the PLS-SEM Algorithm and Bootstrapping was used to analyze the data. The findings demonstrated that while work stress had a positive but negligible impact on turnover intention, job satisfaction and organizational commitment had a negative and significant influence. Furthermore, the findings indicate that organizational commitment is significantly impacted negatively by work stress and positively by job satisfaction. Additionally, whereas organizational commitment can moderate the association between work stress and turnover intention, it cannot mediate the relationship between job satisfaction and turnover intention. This study has a results to provide important managerial implications for managing employees' turnover intention tendencies